DIMENSIONS OF SOCIAL DEVELOPMENT IN THE ERA OF REGIONAL AUTONOMY - Dyah Asri Gita Pratiwi; Didit Susiyanto (Indonesian Journal of Social Work, 2021)
The policy for implementing regional autonomy is part of the government's political will to respond to environmental demands that have undergone changes. This will have significant implications not only for changes in the system of governance, but also for changes in the mental and mindset of local government officials in particular, and all elements of the supporting forces for regional development (stakeholders) in general. In the regional autonomy policy, the government's ability to make public policies is closely related to achieving the goals of regional development. The importance of this policy will affect the development of social development as part of regional autonomy. Thus, it is hoped that every community will participate in social development through various aspects that have been carried out by the government through public policies. Social development in the era of regional autonomy can provide great opportunities to increase community participation in various goals in order to achieve prosperous conditions. However, the challenge of social development in the current era of regional autonomy is how the dimensions of social development in the current era of regional autonomy are.